Efficiency of voluntary auditory-speech memory in younger schoolchildren with different types of dysontogenesis - M. Zvereva; N. Zvereva; E. Balakireva (European Psychiatry, 2022)
Introduction Assessing of voluntary auditory verbal memory, mediated or non-mediated by meaning context is an important component of impaired mental or psychic development estimation in children with different types of dysontogenesis.